2000
DOI: 10.1007/s002130000453
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in the antinociceptive effects of opioids: importance of rat genotype, nociceptive stimulus intensity, and efficacy at the µ opioid receptor

Abstract: That sex differences in the potency and effectiveness of opioids increased with decreases in the opioid's relative efficacy and with increases in the nociceptive stimulus intensity suggests that the relative efficacy of mu opioids as antinociceptive agents is greater in male than female rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
136
3
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 24 publications
15
136
3
3
Order By: Relevance
“…Previous studies have shown that the intensity of the noxious stimulus used in the pain test can influence the magnitude of sex differences in opioid antinociception (Negus and Mello, 1999;Cook et al, 2000;Craft and Bernal, 2001;Barrett et al, 2002), and in nociceptive thresholds (e.g. Aloisi et al, 1995).…”
Section: Effect Of Nociceptive Stimulus Intensitymentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that the intensity of the noxious stimulus used in the pain test can influence the magnitude of sex differences in opioid antinociception (Negus and Mello, 1999;Cook et al, 2000;Craft and Bernal, 2001;Barrett et al, 2002), and in nociceptive thresholds (e.g. Aloisi et al, 1995).…”
Section: Effect Of Nociceptive Stimulus Intensitymentioning
confidence: 99%
“…Sex differences in opioid antinociception also are widely reported in rodents, although they tend to be in the opposite direction to those observed in humans. For example, morphine was significantly more potent or produced a greater effect in male than in female mice (Kavaliers and Innes, 1987;Lipa and Kavaliers, 1990;Candido et al, 1992) and rats (Baamonde et al, 1989;Cicero et al, 1996;Craft et al, 1999;Cook et al, 2000). Variables that may influence the magnitude of sex differences in opioid antinociception in rodents include opioid efficacy/selectivity, intensity of the noxious stimulus used in the pain test, and subject genotype (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After a one-week wash out period, similar experiments were performed with fentanyl. It was reported that repeated use of opioids did not lead to tolerance if the exposure was separated by 5-7 days (Cook et al, 2000, Walker et al, 1999. The rats in the control groups remained as controls in the cross over.…”
Section: Hot Plate Testingmentioning
confidence: 99%